Transforming Graduate School Faculty Development: Insights from Training Needs Analysis - Dio, Eric Arthur (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to identify the training needs of graduate school faculty at a private higher education institution in the Visayas, Philippines. Using a descriptive research design and total enumeration, 48 faculty members from the Arts & Sciences, Business, Education, Engineering, and Nursing programs participated. A survey questionnaire was utilized to gather data on training attended, training needs, motivating and hindering factors, and preferred training pedagogy. Descriptive statistics were employed for analysis. Results showed that most faculty had participated in development training in the past five years, particularly in educational technology, learning management systems (LMS), and research ethics. Despite being highly experienced educators with over 10 years of experience, participants expressed the need for ongoing training. The most attended training included technology use in education, LMS, research ethics, institutional research protocols, research mentoring, proposal writing, rubrics, and assessment methods. Identified training needs were instructional techniques and subject matter mastery (teaching and learning), technology use and LMS (educational technology), research publication, qualitative research, and mentoring/advising (research). Key hindrances to participation included workload, job responsibilities, limited support, cost of training, and amount of time required. Motivating factors were relevant topics, expert speakers, and convenient schedules. Preferred training modes were seminars, certification/diploma courses, and workshops. The study recommends that an effective and comprehensive faculty development program be formulated and adopted to provide continual training that would enhance the skills and knowledge of the faculty, adapting to the current demands of the educational landscape.